2007
DOI: 10.1038/sj.onc.1210364
|View full text |Cite
|
Sign up to set email alerts
|

The role of Gemtuzumab Ozogamicin in the treatment of acute myeloid leukemia patients

Abstract: Gemtuzumab Ozogamicin (GO) is an antibody-targeted chemotherapy agent consisting of the humanized murine CD33 antibody (clone P67.6) to which the calicheamicing1 derivative is attached via a hydrolysable bifunctional linker. GO is able to induce apoptosis in vitro in CD33-expressing cells and it has been approved in USA and in Europe as monotherapy for the treatment of elderly patients (older than 60 years) with relapsed acute myeloid leukemia (AML). GO administered as a single agent has resulted in overall re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…12,13 In addition, a subset of AML patients expressing the MDR phenotype on their AML blasts has been reported to be resistant to gemtuzumab ozogamicin. [14][15][16][17] Therefore, there is a clear unmet medical need for therapeutics that can circumvent these obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, a subset of AML patients expressing the MDR phenotype on their AML blasts has been reported to be resistant to gemtuzumab ozogamicin. [14][15][16][17] Therefore, there is a clear unmet medical need for therapeutics that can circumvent these obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these studies confirmed single-agent activity of GO in a subset of patients; however, overall response rates have generally not exceeded 25% to 35% and have occasionally been quite disappointing, particularly in heavily pretreated patients. [98][99][100][101][102][103] In these studies, GO has usually been given at 2-week intervals. However, early studies indicated that new CD33 binding sites were continuously reexpressed, and surface CD33 levels returned to pretreatment levels within 72 hours after anti-CD33 antibody administration despite antigen internalization and modulation.…”
mentioning
confidence: 99%
“…Similar to non-Japanese studies, the overall remission OR rate for GO monotherapy has been reported as 30% in a Japanese phase II study 2,3 . The following predictive factors affecting the clinical outcome of GO therapy have been identified in previous studies : P-glycoprotein activity and expression 1,4 , multi-drug resistance protein ATP-binding cassette, sub-family C, member 4 , white blood cell WBC count at the start of GO therapy 5 , CD33-antigen loads in peripheral blood PB 6 , duration of initial complete remission 7 , and cytogenetic risk 7 .…”
mentioning
confidence: 51%